2021
DOI: 10.3390/jcm10194515
|View full text |Cite
|
Sign up to set email alerts
|

Development of A Surgical Treatment Algorithm for Breast Reconstruction in Poland Syndrome Patients Considering Severity, Sex, and BMI

Abstract: Introduction: Poland syndrome is a rare, challenging combination of chest wall and breast deformities for reconstructive surgeons and selecting the treatment can prove difficult. This study aims to help surgeons in choosing the best viable option for treatment by sharing our institutional experience and proposing a guiding algorithm. Methods: A retrospective analysis of all patients with Poland syndrome undergoing treatment for breast and chest wall deformities at a single institution between December 2011 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…Due to the inclusion of younger patients with inadequate abdominal donor site volume in this study as well as in a similar work by Mahrhofer, the authors suggested that free DIEP flaps may not be a suitable reconstructive choice in a significant number of patients. 20 , 21 Alternative free flap donor sites, such as from the thigh or gluteal region, may be more suitable depending on the patient’s needs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inclusion of younger patients with inadequate abdominal donor site volume in this study as well as in a similar work by Mahrhofer, the authors suggested that free DIEP flaps may not be a suitable reconstructive choice in a significant number of patients. 20 , 21 Alternative free flap donor sites, such as from the thigh or gluteal region, may be more suitable depending on the patient’s needs.…”
Section: Discussionmentioning
confidence: 99%
“…Цей метод пропонує сприятливі результати для широкого кола пацієнтів [12]. Крім того, супутні патології -атрофія кісток, підшкірної клітковини та молочної залози, можуть вимагати подальших хірургічних втручань, таких як ліпофілінг або силіконові грудні імплантати в ході подальших процедур, особливо в тих випадках, коли первинний імплантат недостатній [13].…”
Section: Resume Poland Syndrome Is a Rare But Serious Condition That ...unclassified
“…Breast reconstruction consisted in one or more surgical steps depending on nipple displacement, asymmetry of breast volume and shape, presence of the clavicle portion of the pectoralis major muscle and patient’s expectation and needs [ 16 ] (Fig. 1 ).…”
Section: Surgical Techniquementioning
confidence: 99%